Dietary Diversity and Associated Factors among Pregnant Women Attending Antenatal Clinic in Shashemane, Oromia, Central Ethiopia: A Cross-Sectional Study. (12th March 2019) - Desta, Melaku; Akibu, Mohammed; Tadese, Mesfin; Tesfaye, Meskerem
Abstract : Background . Maternal dietary diversity is a proxy indicator of maternal nutrient adequacy and improves health outcomes for both mothers and babies. However, little is documented on dietary diversity among pregnant mothers. Therefore, this study assessed diet diversity and associated factors among pregnant mothers attending the antenatal clinic in Shashemane, Oromia, Central Ethiopia. Methods . An institution-based cross-sectional study was conducted on 315 systematically selected pregnant women attending antenatal clinic of Shashemane town in April 2017. Dietary diversity was assessed using a 24 h dietary recall method, and the dietary diversity score was computed for ten food groups. Bivariate and multivariate logistic regressions were computed to identify associated factors of dietary diversity. Result . In this study, only a quarter (25.4%) of pregnant mothers consumed adequate dietary diversity. Mother's tertiary (AOR 3.18; 95% CI: 1.8, 6.35) and secondary (AOR 2.13; 95% CI: 2.32, 8.72) education, household monthly income above 3500 ETB (AOR = 2.24; 95% CI: 1.47, 7.78), livestock ownership (AOR = 4.15; 95% CI: 2.07, 9.86), women who got emotional support from the husband (AOR = 3.49; 95% CI: 1.12, 8.23), and women who participated in the shooping (AOR = 2.54; 95% CI: 3.27, 9.83) were more likely to attain the adequate dietary diversity. Conclusion . The study revealed that the overall consumption of adequate dietary diversity was found to be low. Developing the educational level of women, increasing household income and owning of livestock, increasing husbands' support, and improving women's participation in the shopping are recommended to improve women's adequate dietary diversity.